Powtoon Animation Videos for Writing Skills Era 5.0 - Pristiwati, Rahayu; Prabaningrum, Dyah; Maharani, Annisa Tetty; Dewi Islamy, Amilia Buana; Fauzizah, Ardha Dwi (Institute of Education and Social Research, 2024)
The post-pandemic learning process has undergone significant changes. Teacher professionalism in managing meaningful learning in the 5.0 era requires people who are more than diligent, intelligent, creative and innovative. Powtoon animated video learning media can be a solution to the problems of Indonesian language teachers in Tegal City in accommodating meaningful writing skills learning activities in Era 5.0. Methods of implementing activities include two types of methods, namely training and mentoring methods. The techniques used in implementing this training method are lectures, questions and answers, discussions, problem solving, case studies, and assignments. The techniques in implementing the mentoring method, namely guided practice and independent practice. This community service partner is a teacher at SMA Ihsaniyah Tegal. The evaluation results also show that the training activities have a positive impact on the achievement of indicators of teacher ability in developing Powtoon animated video learning media. In terms of writing skills, Powtoon's animated video learning media is able to describe the complex process of writing, especially in learning Indonesian in detail and detail.